Elijah Walker Halford papers - Halford, Elijah Walker, 1843-1938.
Correspondence, writings, scrapbooks, printed matter, photographs, and other papers concerning Halford's service (1889-1893) as private secretary to President Benjamin Harrison. Also includes a volume of articles from the Indianapolis Journal written by Halford during a trip to Europe in 1887. Correspondents include Chester Alan Arthur, Cassius Marcellus Clay, Calvin Coolidge, Frederick Douglass, Benjamin Harrison, Rutherford Birchard Hayes, Robert Todd Lincoln, William McKinley, Helena Modjeska, James Whitcomb Riley, Theodore Roosevelt, William H. Taft, Lew Wallace, and members of Halford's family.
Soldier and newspaper editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Clay, Cassius Marcellus, -- 1810-1903 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Douglass, Frederick, -- 1818-1895 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Modjeska, Helena, -- 1840-1909 -- Correspondence; Riley, James Whitcomb, -- 1849-1916 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wallace, Lew, -- 1827-1905 -- Correspondence; Halford family -- Correspondence; Indianapolis journal (Indianapolis, Ind. : Daily); American newspapers -- Indiana -- Indianapolis; Europe -- Description and travel; United States -- Politics and government -- 1889-1893.; Newspaper editors; Secretaries, Presidential; Soldiers